Gut microbiota as a novel target for treating anxiety and depression: from mechanisms to multimodal interventions - Ruohan, Zhang; Ruting, Wang; Hongxi, Wu; Zhenjin, Huang; Jiale, Liang; Rongxin, Zhang; Feng, Jiang; Yuanbo, Song (Frontiers in Microbiology, 2025)
The global prevalence of depression and anxiety continues to rise, with major depressive disorder and anxiety disorders estimated to affect approximately 3.1 and 4.8% of the world’s population. Yet current pharmacological treatments demonstrate limited efficacy. This limitation has spurred extensive research into alternative treatment methods. Emerging evidence highlights a complex correlation between gut microbiota (GM) imbalance and mental health disorders. Disruptions in GM may trigger or exacerbate symptoms of anxiety and depression by interfering with communication pathways between the gut and brain. These pathways include neural signaling through the vagus nerve, hormone regulation via the hypothalamic–pituitary–adrenal (HPA) axis, immune responses involving pro-inflammatory cytokines, and metabolic processes related to short-chain fatty acids (SCFAs). Preclinical studies and initial clinical trials indicate promising results for therapeutic interventions targeting gut microbiota. Given that current evidence remains constrained by insufficient depth of understanding regarding underlying mechanisms, this review explores the intricate interactions among the gut microbiota, and brain, highlighting opportunities for advanced therapeutic approaches, focusing on probiotics, prebiotics, postbiotics, synbiotics, dietary modifications, fecal microbiota transplantation (FMT), fecal virome transplantation (FVT), and traditional Chinese medicine (TCM). It elucidates the role of gut microbiota in depression/anxiety and advances therapeutic approaches.